2021
DOI: 10.3389/fenvs.2021.652933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use Change on Gully Erosion Density in the Black Soil Region of Northeast China From 1965 to 2015: A Case Study of the Kedong County

Abstract: Kedong County is typical of the black soil region of northeast China in being highly susceptible to accelerated soil erosion by gullying. Using data sourced from Corona satellite imagery for 1965, SPOT5 for 2005 and GF-1 for 2015, the spatial distribution of gullies in the research area was mapped. Land use data for 1965, 2005, and 2015 were obtained from the topographic map of 1954, and from Landsat images for 2005 and 2015. Over the last 50 years, the extent of gully erosion in the study area has increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…The slope erosion amount and gully density of cultivated land are 625.01 t/km 2 •a and 0.06 km/km 2 larger than that of the forestland, respectively. The low hills that constitute a large proportion of the study area, along with the central plains, contain much cultivated land with low vegetation coverage and the highest level of human activities in the region, leading to the most intensive soil erosion, which was consistent with the results of Li et al (2019) and Jia et al (2019). Forestlands have high vegetation coverage, but are mostly found in areas with steep slopes.…”
Section: Resultssupporting
confidence: 89%
“…The slope erosion amount and gully density of cultivated land are 625.01 t/km 2 •a and 0.06 km/km 2 larger than that of the forestland, respectively. The low hills that constitute a large proportion of the study area, along with the central plains, contain much cultivated land with low vegetation coverage and the highest level of human activities in the region, leading to the most intensive soil erosion, which was consistent with the results of Li et al (2019) and Jia et al (2019). Forestlands have high vegetation coverage, but are mostly found in areas with steep slopes.…”
Section: Resultssupporting
confidence: 89%
“…Among them, cultivated land has the greatest impact, which may be due to the frequent human activities on cultivated land. This result is consistent with some previous studies [50,51]. For example, the results of Ali Azareh et al's study in 2019 showed that slope aspect, lithology, and land use were identified as the most important factors affecting gully sensitivity in Iran by using a maximum entropy model [3].…”
Section: Analysis Of Controlling Factors Of Gully Erosionsupporting
confidence: 91%
“…Gully erosion on the plains was mostly a result of the long gentle slopes gathering a large amount of water, which led to the development of a large number of gullies. The plains had fertile soils and many agricultural areas [ 53 ], so much of the gully erosion was affected by human activity [ 54 ]. The geology, soil, rainfall, hydrology, vegetation and human activities and their interactions all affected gully erosion irrespective of the topography and will therefore be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%